Athletic development: A psychological perspective (Routledge, 2021)
Athletic Development: A Psychological Perspective is an examination of the psychological factors that help or hinder the development of participants in sport. This includes influences such as families, coach-athlete interactions, and transitional episodes on an individual`s pathway in sport. This edited collection of topical chapters shines a unique psychological perspective on the athlete`s development through sport. It explores a range of contemporary themes that influence athlete`s development including: